Editorial: Language research on sustainability, ecology, and pro-environmental behavior - Jennifer Bruder (323066) (2023)
The consolidation of sustainable thinking and formative behavioral change necessitates that all environmental issues be communicated through an effective use of language. The way language is shaped to promote sustainable behaviors influences the feasibility of pro-environmental actions to increasingly prevail. Considering the power language must shape perceptions, attitudes, opinions and identity, means that researchers of these themes have much to offer to those interested in promoting pro-environmental behavior. The research presented in this Research Topic on language and environment is aimed diversely to highlight several rich avenues for future investigations. Other Information Published in: Frontiers in Psychology License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3389/fpsyg.2023.1218961